HUBUNGAN PATRON-KLIEN ANTARA PENGEPUL DENGAN PEMULUNG DI KOTA PEKANBARU - Melsa Angraini; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Collectors and Scavengers are those that utilize waste contained within the communities that continue to multiply due to the increasing number of people each year. Scevenger every day take, looking and buying junk or used items that can be recycled and sold to collectors usual place subsciption. Relations between the two parties create patron-client relationship throught the introduction to survive sell goods to wholesalers. The problems studied is: Who are those who become a colletors and scavenger the relationship between them the method in this reseasch is type and qualitative descriptive accidental sampling method with the subject scavenger that can be found on a colletor. The results showed that the patron-client relationship collectors with scevenger in everyday life occurred the element of intimacy between them, as well as mutually beneficial relationship to the two parties the relationships between them is no dispute because they feel no ane washarmed in this connection.Keywords:Collector, Scavenger, patron, client